2019
DOI: 10.1186/s13075-019-1835-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6 levels reflect the severity of interstitial lung disease associated with connective tissue disease

Abstract: Background Biomarkers have been actively investigated to supplement functional and imaging modalities to predict the severity, therapeutic responsiveness, and progression of connective tissue disease-associated interstitial lung disease (CTD-ILD). This study aimed to evaluate Krebs von den Lungen 6 (KL-6) as a potential biomarker reflecting the severity of CTD-ILD as assessed through computed tomography (CT) and pulmonary function test (PFT) parameters. Methods This ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 25 publications
9
123
2
3
Order By: Relevance
“…Consistent with this paradigm, a number of studies have demonstrated increased titers of anti-cyclic citrullinated peptide (anti-CCP) antibodies in patients with RA-ILD (9)(10)(11)(12). Apart from high titers of anti-CCP antibodies and rheumatoid factor (RF) (13), several studies have shown associations between RA-ILD and alternative biomarkers (many of which are also associated with idiopathic pulmonary fibrosis [IPF] [14]), such as the epithelial cell-derived Krebs von den Lungen 6 (KL-6) antigen (15), matrix metalloproteinase 7 (MMP-7), pulmonary and activation-regulated chemokine (PARC), surfactant protein D (SP-D), and interferon-γ-inducible protein 10 (IP-10/CXCL10) (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this paradigm, a number of studies have demonstrated increased titers of anti-cyclic citrullinated peptide (anti-CCP) antibodies in patients with RA-ILD (9)(10)(11)(12). Apart from high titers of anti-CCP antibodies and rheumatoid factor (RF) (13), several studies have shown associations between RA-ILD and alternative biomarkers (many of which are also associated with idiopathic pulmonary fibrosis [IPF] [14]), such as the epithelial cell-derived Krebs von den Lungen 6 (KL-6) antigen (15), matrix metalloproteinase 7 (MMP-7), pulmonary and activation-regulated chemokine (PARC), surfactant protein D (SP-D), and interferon-γ-inducible protein 10 (IP-10/CXCL10) (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, circulating KL‐6 is shown to be a sensitive marker of the activity of various types of ILD . Emerging evidence has demonstrated that KL‐6 levels correlate with high‐resolution computed tomography (HRCT) findings, pulmonary function test (PFT), and some clinical parameters in connective tissue disease (CTD)‐ILDs, thus reflecting the severity of CTD‐ILD . The poor prognosis of PM/DM‐ILD also has a positive correlation with serum KL‐6 levels …”
Section: Introductionmentioning
confidence: 99%
“…High levels of KL-6 are seen in the sera of patients with idiopathic interstitial pneumonia, drug-induced ILD, pulmonary sarcoidosis, and connective tissue diseaseassociated ILD. 9,10 It has been reported that KL-6 has a high level of sensitivity and specificity for ILD such as idiopathic pulmonary fibrosis (IPF), and serum levels of KL-6 are 70-100% significantly higher in IPF. Analysis of the relationship between KL-6 serum levels and disease activity suggests that KL-6 serum levels are significantly correlated with the severity of the interstitial pneumonia and IPF.…”
Section: Resultsmentioning
confidence: 99%